Chemical composition of hexane and chloroform extracts from Artemisia scopaeformis (International Journal of Biology and Chemistry, 2020)
Research in the field of medicinal products, especially medicinal plants, has been constantly expanding recently. However, to date, health research has not been widely disseminated. This article focus on the analysis of hexane and chloroform extracts of Artemisia scopaeformis by Gas Chromatography and Mass Spectroscopy (GC-MS) technique. Detailed chemical constituents of A. scopaeformis collected in Kazakhstan were investigated for the first time. The quantitative and qualitative analysis of bioactive constituents of the medicinal plant have been made. A. scopaeformis hexane extract contained 4 compounds: methyleugenol (33.87%), hexadecanoic acid, ethyl ester (41.02%), butyl 4,7,10,13,16,19-do cosahexaenoate (11.55%), hexasiloxane, 1,1,3,3,5,5,7,7,9,9,11,11-dodecamethyl- (13.56%). The chloroform extract of A. scopaeformis contained 5 compounds: fluorene, 2,7-bis(1-hydroxyethyl)- (24.28%), p-dimethylaminobenzylidene p-anisidine (14.59%), 3-acetoxy-5-methyl-2-nitro- terephthalic acid, 4-isopropyl ester 1-methyl ester (11.74%), 3,4-diacetyl-2-methyl-4H-thieno [3,2-b] pyrrole-5- carboxylic acid, methyl ester (17.35%), 4H-1,2,4-triazole-3-thiol, 4-(2-fluorophenyl)-5-(1-methylethyl) – (32.04%). The resulting compounds have significant biological properties: antimicrobial, antioxidant, anti-inflammatory.